Photoacoustic Measurement of Ethane with Near-Infrared DFB Diode Laser - Gang Cheng; Yuan Cao; Kun Liu; Gongdong Zhu; Guishi Wang; Xiaoming Gao (Journal of Spectroscopy)
A compact resonant photoacoustic sensor based on a near-infrared distributed-feedback (DFB) diode laser was developed for detection of ethane (C2H6). A DFB laser emission at 5937.25 cm−1 with a power of ∼5 mW was used as an excitation light source for generating the photoacoustic signal. Wavelength modulation and second harmonic detection scheme were employed. Modulation frequency and modulation amplitude were optimized for getting optimum performance. Performance evaluation based on the linearity response of the PAS sensor system with respect to C2H6 concentration levels was performed, and a good linear dependence of the PAS signal on the C2H6 concentration was obtained. A minimum detectable concentration of 9 ppmv was achieved for detection of C2H6 with a lock-in time constant of 10 ms.